Recognition of Diffuse Hepatic Steatosis - Danil Yevdokimov; Viacheslav Gorikhovskii (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2023)
practice, with the liver and spleen being studied in addition to the lungs and heart. Unfortunately, radiologists often do not have the time to assess the density of the liver's structure, as their attention is primarily on the chest organs such as the lungs, heart, and blood vessels in the thorax. To address this issue, a solution could be the development of a tool that uses machine learning technologies and statistical methods to identify organs and their relationships to diagnose diffuse hepatic steatosis on chest CT scans.